2020
DOI: 10.3390/cancers12071949
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Therapy in Oral Mucositis and Potentially Malignant Oral Lesions: A Therapy Towards the Future

Abstract: Photobiomodulation therapy (PBMT) is an effective treatment modality, which has the significant advantage of enhancing a patient’s quality of life (QoL) by minimising the side effects of oral cancer treatments, as well as assisting in the management of potentially cancerous lesions. It is important to note that the major evidence-based documentation neither considers, nor tackles, the issues related to the impact of PBMT on tumour progression and on the downregulation of cellular proliferation improvement, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 75 publications
(111 reference statements)
0
39
0
1
Order By: Relevance
“…Moreover, oral carcinogenesis is found to be mediated by a set of genetic alterations that affect programed cell death, cell division, and DNA repair [5]. Nevertheless, the incidence [1] and mortality [6] of OSCC have not improved remarkably in spite of the advance in surgery and other treatment options [7,8] as well as the recognition of risk factors that cause oral malignancies mentioned above [3][4][5]9]. Considering the high heterogeneity and pathogenicity of OSCC, all these cancer risks appear to be mingled and required to evaluate the disease prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, oral carcinogenesis is found to be mediated by a set of genetic alterations that affect programed cell death, cell division, and DNA repair [5]. Nevertheless, the incidence [1] and mortality [6] of OSCC have not improved remarkably in spite of the advance in surgery and other treatment options [7,8] as well as the recognition of risk factors that cause oral malignancies mentioned above [3][4][5]9]. Considering the high heterogeneity and pathogenicity of OSCC, all these cancer risks appear to be mingled and required to evaluate the disease prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the photoacceptor can absorb photon energy and reach an electronically excited state, leading to a temporary change in both conformation and function. In this way, light, as reviewed in our previous paper, can play with the cell's perspective [30][31][32]. Pastore et al [73] showed increased oxygen consumption in mitochondria irradiated with 632 nm laser light, and Yu et al [74] observed increased activity of mitochondrial complex-III and -IV when low energy light with a 660-nm wavelength was used.…”
Section: Photobiomodulation and Mitochondrial Bioenergeticsmentioning
confidence: 88%
“…In this way, the photoacceptor can absorb photon energy and reach an electronically excited state, leading to a temporary change in both conformation and function. In this way, light, as reviewed in our previous paper, can play with the cell’s perspective [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of more than 170 COVID-19 positive cases found changes in tongue sensation and onset of tongue ulceration to be the most common symptoms [ 24 ]. The use of photobiomodulation therapy (PBMT) in managing oral lesions has been well documented [ 25 ]. Also, the specific use of PBMT as an effective treatment in COVID-19 patients was reported by Soheilifar and colleagues [ 26 ].…”
Section: Discussionmentioning
confidence: 99%